SPEECH ACT: THE USE OF DCT INVENTORY ON RESEARCHING REFUSAL AND COMPLAINTS - Kasdi, Jonri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
The specific speech act instruction could lead to greater pragmatic competence for speakers. It suggests that teachers could use DCTs in the classroom to focus on social distance between speakers, and then use role play activities to mimic an authentic situation, beginning with the more semantically formula apologies and requests. These speech acts may be easier for students to acquire than refusals and complaints, which demand more social interaction as well as many face-saving moves. The instrument is The Discourse Completion Test, or DCT, was composed of six prompts. Four prompts were created to elicit the specific speech acts comprising the focus of the study, complaints and refusals; two distractors were also included. (These distractors elicited an apology and a request, and are not included in the results of the study). Moreover, the subjects are Indonesian colleagues, who study at university across Malaysia. Ninety percent of them are female respondents, which researcher accidentally met at various places (campus, meeting, restaurant, and house). The overall males and females consist of 15 persons; 9 persons female and 6 persons male.